Stability of Pure Biodiesel (B100), Biodiesel Mixture (B40), and Petroleum Diesel (B0) Due to Storage - Mufidah, Zunanik; Tiguna, Amril Hakim; Haryanto, Agus (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Biodiesel is produced from synthetic ester compounds of vegetable and animal oils through a process of refining, bleaching, degumming, transesterification, and esterification. The quality and characteristics of the fuel are greatly influenced by the storage. The purpose of this research is to determine and analyze the effect of storage conditions on the physical and chemical changes of biodiesel (B100), biodiesel blend (B40), and petro diesel (B0). Experiment was conducted by storage fuels using glass bottle for 35 days arranged into four conditions based on cap and wrapping using aluminum foil, namely P1 (with cap, with wrapping), P2 (with cap, no wrapping), P3 (no cap, with wrapping), and P4 (no cap, no wrapping). Results showed that fuel quality decreases due to storage indicated by an increase in water content, density, acid number, and color parameters, as well as a decrease in the specific calorific value of all fuels. The condition of the storage container affected the changes the quality parameters. Based on its impact on fuel quality decline, the order of storage container conditions from the best is P1 (with cap, with wrap) > P2 (with cap, no wrap) > P3 (no cap, with wrap) > P4 (no cap, no wrap). Keywords: Biodiesel, Biodiesel blend (B40), Diesel fuel, Stability, Storage time.